Curriculum Administration: Systemic Foundations for the Effectiveness of Islamic Education in the Modern Era - Farkhan, Muhammad Nur; Askina, Julia Muti; Ainaya, Syamila; Ridlo Dina Yuliana, Anaas Tri (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2025)
Islamic education plays a strategic role in forming a generation of Muslims who are faithful, knowledgeable, and have noble character. To achieve this goal, curriculum administration is a crucial component that must be managed professionally and systematically. In the midst of globalization and the rapid development of technology, Islamic educational institutions are required to continue to innovate in order to remain relevant and competitive. Unfortunately, curriculum administration is often overlooked, even though it has a significant role in determining the effectiveness and quality of education. This article aims to explore the urgency of curriculum administration in the development of effective and quality Islamic education. This research uses the literature study method by analyzing various literature sources, such as books, scientific journals, articles, and relevant policy documents. The results of the study show that curriculum administration in Islamic education must be able to integrate Islamic values holistically into all aspects of learning. In addition, continuous evaluation of the development of learners' soft skills is an important part of ensuring that religious knowledge can be implemented in real life. With good curriculum administration management, Islamic education has the potential to produce graduates who are not only intellectually intelligent, but also superior in morality and readiness to face the challenges of the times.